Multiple linear regressions on determinants of ginger production in yeki district, Sheka Zone, South West Ethiopia - Alemu Bekele Eticha (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Ginger is an important crop that is produced worldwide for both spice and medicine. Ethiopia is one of the sub-Saharan countries which cultivate and export ginger to other countries. Even though ginger is an essential spice in the country, constraint faced during production reduces its output. Thus, this study aimed to identify the determinants of ginger production in the case of Yeki woreda. Primary data were collected using a self-administrative questionnaire administered on 110 ginger producers selected using a simple random sampling technique. Furthermore, data analysis methods descriptive statistics and multiple linear regressions were applied. The mean value of ginger yield was 51.74 quintals. The empirical result discovered that fertilizer use (p<0.001), bacteria disease (p<0.0340), education levels (p<0.0001, <0.0001, <0.0009, <0.0034), farm size (p<0.0025), farmer experience (p<0.0003), and weeds (p<0.0018) were significant predictor variables in determining ginger production. Moreover, the result revealed that 85.00% of the discrepancy of ginger production explained by the independent variables included in the multiple linear regression model. Generally, fertilizer use, farm size in a hectare, the experience of farmers, weeds effect, diseases like bacteria wilt, and education level of farmers were the significant factors of ginger output. Therefore, the study recommends the implementation and improvement of ginger production at the producer level by considering the use of fertilizer, farm size, herbicides, education level of farmers, and control bacterial wilt disease. Thus, developmental institutions, agricultural extensions, and governments are advisable to improve the yield of ginger production via controlling the significant determinants.